Participatory variety selection and multiplication of early generation seed of cereals and food legumes for mixed farming system in North Shoa, Ethiopia - Shibabaw, Belayneh; Mulugeta, Tesfaye; Tefera, Neway; Tiruneh, Altaye; Taye, Kefyalew; Bezabih, Aemiro; Chaklie, Shumet; Takele, Emebiet; Kassa, Yehuala; Mamo, Dejenie; Managido, Demis; Aynewa, Yetsedaw; et al. (Amhara Regional Agricultural Research Institute, 2023)
The highlands of North Shoa in Amhara region are dominated by cereals (wheat, barley and tef) followed by food legumes. The productivity of cereals and food legumes is low due to biotic and abiotic factors as well as insufficient input supplies like certified seed, inoculants, and other inputs. Because of diseases and insect pests, acidity and water logging problems, farmers are reducing areas of food legumes and growing more cereals leading to low crop diversity leading to reduced soil fertility, incomes, and food diversity. Several cereal and food legume varieties are released by many centres but did not reach farmers due to limited demonstration to create awareness and demand and shortage of quality early generation seed. The poor access to quality seed contributes to low crop productivity.